Balanced use of fertilizers: A key for sustaining crop productivity and soil quality - Wanjari, R H; Kumar, Dhiraj; Singh, Muneshwar; Nagwanshi, Anil (Indian Farming, 2022)
Long term fertilizer experiments (LTFEs) conducted across the country illustrated that it is difficult to maintain the pace of productivity to satisfy the food demand of the population without using chemical fertilizers. Results indicated that balanced and integrated nutrient management (INM) improved soil quality which resulted in enhancement of nutrient-use efficiency, grain quality and sustainable crop productivity irrespective of cropping system and soil type. Application of 100% NPK supplemented with Zn and S as per need in major cropping systems sustained the yield. Production was further enhanced by using farmyard manure (FYM) along with recommended dose of fertilizer. Nutrient application either through balanced fertilizer use or INM (100% NPK + FYM) improved soil organic carbon (SOC), physical condition and biological status of soil. Sustainable yield index obtained with balanced and INM was higher over imbalanced fertilizer nutrition. Thus, balanced use of fertilizers is most suitable nutrient application option to sustain crop productivity and soil quality in our country.